Kebutuhan Anak Sekolah Dasar dalam Membaca Permulaan pada Masa Pandemi COVID-19 di Perkampungan Kayu Besar Jakarta - yeni rahmania; Khusnul Fatonah (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This study aims to determine the types of early reading needs in elementary school children (SD) in the Kayu Besar Village, West Jakarta and to find out the various obstacles experienced by parents in meeting their children's early reading needs. The type of research used is qualitative using descriptive method. The research subjects consisted of six informants which included three grade II elementary school children who had low early reading skills and the three parents of the child. Researchers collect data by interview, observation, and documentation. Interviews were conducted with all informants. Participation observations were made to three informants by observing learning activities carried out at their respective homes. The results showed that the needs of elementary school children in early reading in Kayu Besar Village had not been met. These needs include a lack of attention from families and school teachers, unmonitored child development and growth, inadequate learning facilities, and unfavorable and boring learning conditions. Meanwhile, the obstacles for parents in meeting the needs of elementary school children in early reading in the Kayu Besar Village, West Jakarta, include the parents being unable to fully share their attention in assisting their children in learning, the inability to provide learning facilities due to low incomes, and the lack of education provided by parents. The biggest obstacle experienced by parents in meeting the needs of elementary school children in early reading is related to the low income of parents and the minimal education provided by parents so that they cannot help children in overcoming difficulties in learning to read early.